Performance of Sunray Organic Fertilizer on the Growth and Yield of Wetland Rice - Aziz, MA; Miah, MAM; Sayem, SM (Journal of Agriculture & Rural Development, 2008)
The experiment was conducted at Bangladesh Rice Research Institute farm, Gazipur during the T. aman season, 2003 in order to determine the performance of Sunray organic fertilizer on the growth and yield of rice. The following eight treatment combinations were tested in wetland condition: T1= Native nutrient; T2 = Sunray Formula + G (SF) @ 100 kg/ha + Sunray Padiplus (PP) 20 ml @ 10 ml/4.5 lit./100m2 + Sunray Pady Segar (PS) @ 150 kg/ha + ( STB - N, P, K, S & Zn content in SF, PP & PS); T3= STB for high yield goal (HYG); T4= STB + 20 ml PP; T5= STB + 10 ml PP; T6= SF @ 400 kg/ha + ( STB - N, P, K, S & Zn content in 400 kg SF); T7= PS @ 400 kg/ha + (STB - N, P, K, S & Zn content in 400 kg PS ); T8= SF @ 200 kg/ha + PS@ 200 kg/ha + 10 ml PP + ( STB - N, P, K, S & Zn content in SF, PS and PP). The blanket doses of fertilizers were applied on soil test based (STB). BRRI dhan31 was used as test crop. The sources of N, P, K, S & Zn were Urea, TSP, MP, gypsum and zinc sulphate. Urea was applied into three equal splits, 1/3rd basal, 1/3rd maximum tillering stage and the remaining 1/3rd at panicle initiation stage. The treatment T2 where Sunray fertilizer were applied in combination with chemical fertilizer on STB produced substantially higher yield than those of other tested treatments. In terms of economic point of view this treatment also be considered as the most viable treatment in the experiment. Key words: Sunray, organic fertilizer, growth and yield, wetland rice.